Removing Cultural Impediments to Entrepreneurship: Policy Implications For Indonesia - Balbir Bhasin; Lee Keng Ng; Mohamad Zainuba (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
Though cultural explanations as determinants of economic outcomes have mainly been ignored by researchers (Guiso et al., 2006), national culture, on the other hand, has been proven to have a direct and identifiable impact on the level of entrepreneurial behavior (Kreiser et al.,2002).With more than 300 ethnic groups, each with their own language and dialect, Indonesia is a unique case of classical cultural diversity. Indonesian culture embraces collectivism and the traditional values of Hinduism, Buddhism and Islam, belief systems which inherently function against the fostering of entrepreneurial spirit (Dana, 1995). Removing impediments to entrepreneurship is a key challenge for the government. Using Indonesiaas a case in point, this paper assesses the influence culture has on entrepreneurship and explores initiatives and measures that can be used to strengthen inherent cultural values that stimulate entrepreneurship, encourage risk-taking, and in turn promote economic development.